Research trends on microgrid systems: a bibliometric network analysis - Handrea Bernando Tambunan; Nur Widi Priambodo; Joko Hartono; Indra Ardhanayudha Aditya; Meiri Triani; Rasgianti Rasgianti (Institute of Advanced Engineering and Science, 2023)
The numeral of academic publications in the microgrid system field has rapidly grown. A microgrid system is a group of interconnected distributed generation, loads, and energy storage operating as a single controllable entity. Many published articles recently focused on distributed generation, system control, system stability, power quality, architectures, and broader focus areas. This work analyzes microgrid: alternating current (AC), direct current (DC), and hybrid AC/DC microgrid systems with bibliometric network analysis through descriptive analysis, authors analysis, sources analysis, words analysis, and evolutionary path based on the Scopus database between 2010 and 2021. The finding helps find out the top authors and most impact sources, most relevant and frequently used in the research title, abstract, and keyword, graphically mapping the research evolved and identifying trend topic.